2011
DOI: 10.1088/0957-4484/22/18/185304
|View full text |Cite
|
Sign up to set email alerts
|

The effect of random copolymer on the characteristic dimensions of cylinder-forming PS-b-PMMA thin films

Abstract: The block copolymer self-assembly approach has received great attention in recent years as a possible way to overcome the limits of conventional lithography and to fabricate sub-22 nm structures. At this level, precise nanometric control is crucial for technological applications and the search for a flexible and reproducible protocol is a great challenge. The polystyrene-b-poly(methylmethacrylate) (PS-b-PMMA) system, with a styrene fraction of 0.71, spontaneously separates into a periodic array of hexagonally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 23 publications
3
47
1
Order By: Relevance
“…22,23 The average pore diameter in the final polymeric film deposited on the RCP depends on the duration of the O 2 plasma treatment that is necessary to remove the RCP from the bottom of the pores and completely open the mask. 47 In this regard, a thin RCP layer would result in a relatively short O 2 plasma exposure and consequently a minimization of the pore enlargement caused by the isotropic etching. …”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…22,23 The average pore diameter in the final polymeric film deposited on the RCP depends on the duration of the O 2 plasma treatment that is necessary to remove the RCP from the bottom of the pores and completely open the mask. 47 In this regard, a thin RCP layer would result in a relatively short O 2 plasma exposure and consequently a minimization of the pore enlargement caused by the isotropic etching. …”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…They demonstrated pore diameters ranging from 20 nm to 30 nm by increasing molecular weight by a factor of two. Similarly, Andreozzi et al [23] studied the evolution of the mean pore diameter in the polymeric films as a function of the oxygen plasma irradiation time. They showed that a different compositions of the random copolymers, induced variations of the dimensions of the nanopores in the PS matrix.…”
Section: Effect Of Bcs Periodicitymentioning
confidence: 99%
“…The hole formation was also studied over the past. Guarini and Andreozzi [22,23] investigated the influence of process parameters on the self-assembly process for PS/ PMMA System, focusing on the distribution of the pore diameters, and the pore spacing across the film. In this article we investigate the dynamics of BCP S-A, using an in-plane analysis technique (CD-SEM) by following the evolution of the critical dimension (CD) and the hole circularity in the finale template as function of the processing parameters, which to the best of our knowledge has not been reported so far.…”
Section: Introductionmentioning
confidence: 99%
“…The PMMA cylinders were selectively removed through immersion in acetic acid bath and subsequent rinsing in deionized water. O 2 plasma treatment was subsequently used to remove the brush layer from the bottom of the nanopores and to guarantee a good adhesion between the SiO 2 substrate and the evaporated Si (Andreozzi et al 2011b). The random copolymers and the block copolymers were marked as R62, R58, and B71 where R and B stand for random and block, respectively, and the numbers represent the percent of styrene units.…”
Section: Polymeric Mask Preparationmentioning
confidence: 99%